2020
DOI: 10.1371/journal.pone.0237382
|View full text |Cite
|
Sign up to set email alerts
|

The arch support insoles show benefits to people with flatfoot on stance time, cadence, plantar pressure and contact area

Abstract: Background Pes planus (flatfoot) is a common deformity characterized by the midfoot arch collapses during walking. As the midfoot is responsible for shock absorption, persons with flatfoot experience increased risk of injuries such as thumb valgus, tendinitis, plantar fasciitis, metatarsal pain, knee pain, lower-back pain with prolonged uphill, downhill, and level walking, depriving them of the physical and mental health benefits of walking as an exercise. Methods Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
3
14
0
1
Order By: Relevance
“…The present study showed that, compared to the flat insole, the stance time with the PPRI was reduced when level walking at slow gait speed (0.8 m/s). Huang et al pointed in the research of prefabricated insoles that the shortening of stance time within the range of gait balance shows benefits for gait efficiency [17], which was consistent with the aforementioned results of this study. However, with the increase in gait speed, compared with the other two insoles, the stance time when wearing PPRI did not decrease and remained basically the same.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present study showed that, compared to the flat insole, the stance time with the PPRI was reduced when level walking at slow gait speed (0.8 m/s). Huang et al pointed in the research of prefabricated insoles that the shortening of stance time within the range of gait balance shows benefits for gait efficiency [17], which was consistent with the aforementioned results of this study. However, with the increase in gait speed, compared with the other two insoles, the stance time when wearing PPRI did not decrease and remained basically the same.…”
Section: Discussionsupporting
confidence: 93%
“…Some previous studies have confirmed that customized insoles can be used as an auxiliary physiotherapy tool, which has a positive effect on helping subjects change their gait and re-adjust the pressure distribution on the pelma [ 14 , 15 , 16 , 17 ]. Designing customized insoles based on plantar pressure can specifically help users change the abnormally distributed pressure on the plantar, which is one of the most common traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…The 3D printed heel support insoles fabricated by Jin, et al [ 43 ] for healthy individuals and the 3D printed insoles fabricated by Tarrade, et al [ 44 ] for workers also found a significant reduction in peak pressure over the hindfoot region. It was anticipated that the midfoot pressures were increased because of the arch support, which is consistent with other similar studies [ 42 , 43 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Available reports on the effectiveness of various physiotherapeutic techniques on dynamic foot indicators do not analyze the impact of applied therapies on gait phases in relation to flat feet with pain. However, such an analysis seems to be warranted, because, as it has already been mentioned, incorrect arching of the foot and related pain may affect the biomechanics of gait by disturbing the pressure of the feet on the ground 2 , 47 . In our research, we assessed the effectiveness of the proposed 4-week therapies.…”
Section: Discussionmentioning
confidence: 99%